Variability in Postural Control With and Without Balance-Based Torso- Weighting in People With Multiple Sclerosis and Healthy Controls. Issue 10 (1st October 2014) - Hunt, Charlotte M.; Widener, Gail; Allen, Diane D.
Abstract : Background: People with multiple sclerosis (MS) have diminished postural control, and center of pressure (COP) displacement varies more in this population than in healthy controls. Balance-based torso-weighting (BBTW) can improve clinical balance and mobility in people with MS, and exploration using both linear and nonlinear measures of COP may help determine whether BBTW optimizes movement variability. Objective: The aim of this study was to investigate the effects of BBTW on people with MS and healthy controls during quiet standing. Design: This was a quasi-experimental study comparing COP variability between groups, between eye closure conditions, and between weighting conditions in the anterior-posterior and medial-lateral directions. Methods: Twenty participants with MS and 18 healthy controls stood on a forceplate in 4 conditions: eyes open and closed and with and without BBTW. Linear measures of COP displacement included range and root mean square (RMS). Nonlinear measures included approximate entropy (ApEn) and Lyapunov exponent (LyE). Three-way repeated-measures analyses of variance compared measures across groups and conditions. The association between weighting response and baseline nonlinear variables was examined. When significant associations were found, MS subgroups were created and compared. Results: The MS and control groups had significantly different range, RMS, and ApEn values. The eyes-open and eyes-closed conditions had significantly different range and RMS values. Change with weighting correlated with LyE ( r =−.70) and ApEn ( r =−.59). Two MS subgroups, with low and high baseline LyE values, responded to BBTW in opposite directions, with a significant main effect for weighting condition for the LyE variable in the medial-lateral direction. Limitations: The small samples and no identification of impairments related to LyE at baseline were limitations of the study. Conclusions: The LyE may help differentiate subgroups who respond differently to BBTW. In both subgroups, LyE values moved toward the average of healthy controls, suggesting that BBTW may help optimize movement variability in people with MS.